Experience of endoscopic thyroidectomy in a single‐centre institution. Issue 4 (November 2016) - Tai, Dora KC; Chick, Wai‐Keung; Chan, Peter CM; Lau, Chi‐Hung; Tang, Donald LC
Abstract : Aim: Endoscopic thyroidectomy has been applied to various thyroid diseases to improve the cosmetic outcome of patients. Our centre has adopted the bilateral axillo‐breast approach for certain thyroid diseases. The aim of the present study was to report our experience of endoscopic thyroidectomy in comparison with open thyroidectomy to compare outcomes, complications and feasibility. Patients and Methods: Between January 2011 and December 2014, a total of 47 patients underwent endoscopic thyroidectomy for benign thyroid diseases. From January 2013 to December 2013, a total of 60 patients who underwent open thyroidectomy with the same criteria as endoscopic thyroidectomy patients were included as the control group. Age, sex, tumour size, operative time, length of hospital stay and postoperative complications were analysed. Results: There was no statistically‐significant difference in terms of age, sex or size of thyroid nodule between the two groups. The majority of surgeries in both groups were hemithyroidectomies (87.2 per cent in the endoscopic group and 81.7 per cent in the open thyroidectomy group). The mean operative time for the endoscopic group was significantly longer than that of the open thyroidectomy group (238.2 + 73.6mins vs 120.2 + 38.8 min, P < 0.001). The length of hospitalization was also longer in the endoscopic group (mean: 5.1 + 1.4 days vs 3.7 + 1.6 days, P < 0.001). Regarding postoperative complications, there was no statistically‐significant difference in terms of hypocalcaemia, recurrent laryngeal nerve injury, skin numbness, skin burn or seroma formation. Conclusion: Endoscopic thyroidectomy is a safe operative procedure, and is a feasible alternative to open thyroidectomy for benign thyroid tumours.